2014
DOI: 10.1186/s13058-014-0470-2
|View full text |Cite
|
Sign up to set email alerts
|

Profiling gene promoter occupancy of Sox2 in two phenotypically distinct breast cancer cell subsets using chromatin immunoprecipitation and genome-wide promoter microarrays

Abstract: IntroductionAberrant expression of the embryonic stem cell marker Sox2 has been reported in breast cancer (BC). We previously identified two phenotypically distinct BC cell subsets separated based on their differential response to a Sox2 transcription activity reporter, namely the reporter-unresponsive (RU) and the more tumorigenic reporter-responsive (RR) cells. We hypothesized that Sox2, as a transcription factor, contributes to their phenotypic differences by mediating differential gene expression in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…The signaling cascade finally activates the anti-apoptotic factor Bcl and the inhibitory apoptotic factors Bad and Bax [25e28]. Furthermore, a recent study showed that Sox2 has the ability to bind the promoter region of ErbB2 [29]. These previous results support our findings that Sox2 promotes SGC survival through ErbB signaling.…”
Section: Discussionsupporting
confidence: 89%
“…The signaling cascade finally activates the anti-apoptotic factor Bcl and the inhibitory apoptotic factors Bad and Bax [25e28]. Furthermore, a recent study showed that Sox2 has the ability to bind the promoter region of ErbB2 [29]. These previous results support our findings that Sox2 promotes SGC survival through ErbB signaling.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, we asked if the dichotomy of RU and RR also exists in primary patient samples. Four cases of fresh, previously untreated TNBC patient samples were processed and infected with the SRR2 reporter using a protocol described previously [ 8 ]. As shown in Figure 4C , we detected a small (1.1 to 3.8%) RR cell subset in all cases examined.…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, it was demonstrated that enforced expression of Sox2 in breast cancer cells contributes to enhanced proliferation and invasion in vitro , and tumor formation in xenograft mouse models [ 4 , 5 ]. In studies reported by us, we found that the transcriptional activity of Sox2, detectable by the Sox2 regulatory factor-2 (SRR2) reporter, is found only in a small subset of cells in estrogen receptor-positive breast cancer cell lines and patient samples [ 7 , 8 ]. This has since been confirmed in studies by other groups [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…CD133 and ALDH1) that change rapidly in response to cellular conditions are used to isolate cancer stem cells. To illustrate this point, we focus on CD133, which has been linked with SOX2 expression and cancer stem cells in many tumor cell types [ 85 91 ]. In 2003, CD133 was reported to serve as a marker for the tumor-initiating cells of brain tumors.…”
Section: Expression and Function Of Sox2 In Cancermentioning
confidence: 99%